Performance Evaluation of Digital Telecommunications Systems by Joint Simulation of Modulation and Channel Coding with Graphical Interface Tools - Solgada, Ruhel (2024)
Digital telecommunications systems are part of the critical infrastructure required by developing countries to close the digital divide. The practical evaluation of the quality of these systems is a transcendent issue, ensuring that educational, health, security, and other services meet established standards. In a digital telecommunications system, the digital modulation and channel coding blocks are directly related to performance in terms of the bit error probability, which reflects the quality perceived by the recipient of the service. In the present article, the joint simulation of the mentioned blocks is carried out, and the respective Bit Error Rate (BER) is evaluated. The simulation is validated by comparison with the bit error probability of the system. Furthermore, two graphical interface tools are presented, allowing a comprehensive understanding of i) the production of errors in the constellation due to AWGN noise; and ii) the correction of errors in a transmitted image, based on the specific value of the signal-to-noise ratio.